Factors Affecting Birth Space Interval of Women Who Are Attending Primary Health Care Centers - Hassoon, Suhair (Iraqi National Journal of Nursing Specialties, 2010)
Objective: The aim of this study is to determine the factors affecting birth space interval in a sample of women. Methodology: A cross-sectional study conducted in primary health centers in Al-Tahade and Al- Shak Omar in Baghdad city. Data were collected by direct interview using questionnaire especially prepared for the study. Sample size was (415) women in age group (20-40) years who were chosen randomly. Results: Analysis of data shows highest rate of women (31.8%) had a birth space interval of (8-12) months followed by (26.7%) had a birth space interval of (19-24) months, (20.2%) had a birth space interval of (>24) months and (16.1%) had a birth space interval of (13-18) months respectively, while lower rate of women (5.1%) had birth space interval of (7) months. The birth space interval was higher in age group (20) years. Also, this interval was prolonged by the use of contraceptives, breast feeding and women who had a high level of education. Analysis of data shows that (age group, level of education, occupation, use of contraceptives, parity and number of abortion) were significant factors associated with birth space interval by using P-value of less than 0.01 was considered significant to test the result. Recommendations: Concentrated effort should be made to emphasize the risk of close birth spacing for both of the mother and infant, in all our primary health centers as well as the family planning centers should be included in these efforts explaining the importance of breast feeding for adequate birth spacing.